Assessment of functional behavior of children with autism spectrum disorders in early age in collaboration with families and speech therapists - Grigėnaitė, Julija (Special Education, 2020)
The aim of the research presented in this article is to reveal the possibilities of applying the methodology of the assessment of functional behavior of children with autism spectrum disorders in early age in collaboration with specialists (speech therapists) and parents. The research involved 16 speech therapists working in health and education systems.
Keywords: autism spectrum disorder; early intervention; assessment of functional behavior